PEMBUKTIAN TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN SECARA PEMBELAAN TERPAKSA MELAMPAUI BATAS - faris laia (JURNAL PANAH KEADILAN, 2026)
Proving a criminal charge of murder committed under circumstances of excessive necessary defense involves determining whether the act of taking another person's life meets the elements of the crime of murder or falls under a justification that negates the unlawfulness of the act. This study employs a normative legal research method, utilizing both conceptual and statutory approaches. The objective of the research is to examine the evidentiary process regarding murder committed through excessive necessary defense. The findings indicate that while the evidentiary process is rigorously conducted by law enforcement given that murder is inherently an unlawful act it is crucial to recognize the role of "excusing grounds" in criminal law. These grounds serve to protect individuals who, while outwardly committing a criminal act, lack the internal capacity to be held accountable for their actions. The application of such excusing grounds requires caution, necessitating strict adherence to statutory provisions and careful consideration of the specific facts of each case. Law enforcement officials must meticulously examine all facts, evidence, and the perpetrator's psychological state at the time of the incident to verify whether a situation of excessive necessary defense actually occurred.